How to calculate information quantity on the life quality in the values ecological factors? - E. V. Lutsenko; V. I. Loiko; T. P. Baranovskaya (Новые технологии)
There are a large number of different indicators (particular criteria) of the life quality and various ways of their aggregation in an integral criterion. There are also a large number of different standards of quality of life at various levels: from urban to national and international. However, in all these standards, the availability of indicators characterizing the quality of the natural environment is general, i.e. environmental factors. The problem is that both quality of life indicators and environmental factors are described in different types of scales (nominal, ordinal and numerical) and in different units of measurement, and how to process them in one model is not clear. Traditionally, only numeric indicators are used which, for processing, are normalized in relative units relative to the range of variation of the quantity and aggregated as average geometric indicators or simply average ones. According to the authors, both the first and the second are incorrect, because they neutralize the effect of various environmental factors on the quality of life, which leads to a loss of information on the strength and sign of the influence of environmental factors on the resulting indicators that characterize the quality of life. To solve this problem it is proposed: 1) not to discard the indicators measured in nominal and ordinal scales, but to increase their degree of formalization to numerical ones and then process them together with numeric ones, this provides the possibility of sharing different types of scales in one model; 2) to ensure the comparability of the processing of indicators measured in different units of measurement by the fact that they are all transformed into one unit of measure: the unit of information; 3) to use as an integral criterion not the average one, but the amount of information in the values of environmental factors about the values of indicators that characterize the quality of life. However, this approach has not been considered in the literature. The article is aimed at completing this gap.